Object detection with deep learning in real world scenario - Lim, Yen Yong (Nanyang Technological University, 2023)
Object detection with deep learning has evolved over the years and continues to be a popular area of research with newer models being released frequently, surpassing its predecessors. However, despite these advancements, there is still a lack of findings on the strengths and weaknesses of different models and how these models compare with each other. There is also a lack of research on how different fine-tuning methods affect the performance of these models.